E17 Diffusion Weighted Imaging Study Of Prefrontal Cortex White Matter In Prodromal Huntington Disease. (17th September 2014) - Kim, R; Matsui, J; Wassermann, D; Vaidya, J; Johnson, H; Magnotta, V; Long, JD; Mills, JA; Lowe, M; Sakaie, K; Rao, S; Smith, M; et al.
Abstract : Background: There is considerable interest in finding reliable indicators of Huntington's disease (HD) progression to judge the efficacy of novel treatments that slow or stop disease onset before debilitating signs appear. Diffusion-weighted imaging (DWI) may provide a reliable marker of disease progression by characterising diffusivity changes in white matter (WM) in individuals with prodromal HD. The prefrontal cortex (PFC) may play a role in HD progression due to its prominent striatal connexions and documented role in executive function. Aims: The primary goal is to assess alterations in the white matter tracts of HD gene-positive individuals using DWI and examine its association with motor, cognitive, psychiatric, demographic and genetic variables. Methods: Imaging and clinical data were collected from 15 PREDICT-HD sites. This study uses DWI to characterise diffusivity in specific regions of PFC WM defined by FreeSurfer in 53 prodromal HD participants and 34 controls. A streamline-specific alteration was assessed in four major PFC WM tracts: forceps minor (FM), anterior thalamic radiations (ATR), inferior fronto-occipital fasciculi (IFO), uncinate fasciculi (UNC). Results: Statistically significant increases in mean diffusivity (MD) and radial diffusivity (RD) among CAP groups relative to controls were seen in inferior and lateral PFC regions. White matter alterations in FM, ATR, and IFO showed robust associations with neuropsychological measures of executive functioning. Conclusions: The gradient of effects that tracked with CAP group suggests DWI may provide markers of disease progression with increasing diffusivity abnormalities in the lateral PFC of prodromal HD individuals. Our tract study also suggests that long-range tracts that are essential for cross-region information that shows early vulnerability in HD and may help to explain cognitive problems in the prodromal stage. Funding: National Institutes for Health, National Institute of Neurological Disorders and Stroke 040068, and CHDI Foundation, Inc. Reference: Matsui JT, Vaidya JG, Johnson HJ, et al . Diffusion weighted imaging of prefrontal cortex in prodromal huntington's disease. Human Brain Mapping 2013;1–12:doi:10.1002/hbm.22273